Glasblåsarna på Melchior Jungs glasbruk i Stockholm - Ramström, Annica (Hikuin, 2010)
The glasblowers at Melchior Jungs glassware in Stockholm By Annica Ramström In year of 1641 Melchior Jung founded a glasswork in Stockholm. His idea was to make the same kind of luxurious glasses that were made in Italy. The glass made in Sweden was a kind of glass called waldglas, green- or brown colored glass. The glassblowers in Sweden were not able to produce this kind of clear glass so Melchior Jung travelled to Paris to hire more skilled craftsmen. He found some Italian glassworkers that were interested in the idea. But when they arrived to Sweden they disappeared in just a few months. He hired some new Italian glassblowers in Paris but the same thing happened again, they disappeared. To try and understand what made the Italians run away, Homi K Bahbah’s theories about cultural distress have been used. Especially the terms unhomely and third space is used in this article. The cultural differences between the Italians and the Swedes were hard to over-bridge. It was not only the material world that was different, there were also different norms and values to comprehend. If the Italians and the Swedes had been able to create what Bahbah calls the third space the outcome might have been different and the Italians would have stayed. Third space is a space were new rules and norms are negotiated forth. It is not a blending of two original elements that form a third, but a space where completely new positions are developed.